Phylogenetic placement of environmental sequences using taxonomically reliable databases helps to rigorously assess dinophyte biodiversity in Bavarian lakes (Germany). (17th October 2019) - Gottschling, Marc; Chacón, Juliana; Žerdoner Čalasan, Anže; Neuhaus, Stefan; Kretschmann, Juliane; Stibor, Herwig; John, Uwe
Abstract: Reliable determination of organisms is a prerequisite to explore their spatial and temporal occurrence and to study their evolution, ecology, and dispersal. In Europe, Bavaria (Germany) provides an excellent study system for research on the origin and diversification of freshwater organisms including dinophytes, due to the presence of extensive lake districts and ice age river valleys. Bavarian freshwater environments are ecologically diverse and range from deep nutrient‐poor mountain lakes to shallow nutrient‐rich lakes and ponds. We obtained amplicon sequence data (V4 region of small subunit‐rRNA, c . 410 bp long) from environmental samples collected at 11 sites in Upper Bavaria. We found 186 operational taxonomic units (OTUs) associated with Dinophyceae that were further classified by means of a phylogenetic placement approach. The maximum likelihood tree inferred from a well‐curated reference alignment comprised a systematically representative set of 251 dinophytes, covering the currently known molecular diversity and OTUs linked to type material if possible. Environmental OTUs were scattered across the reference tree, but accumulated mostly in freshwater lineages, with 79% of OTUs placed in either Apocalathium, Ceratium, or Peridinium, the most frequently encountered taxa in Bavaria based on morphology. Twenty‐one Bavarian OTUs showed identical sequences to already known and vouchered accessions, two of which are linked to type material, namely Palatinus apiculatus and Theleodinium calcisporum . Particularly within Peridiniaceae, delimitation of Peridinium species was based on the intraspecific sequence variation. Our approach indicates that high‐throughput sequencing of environmental samples is effective for reliable determination of dinophyte species in Bavarian lakes. We further discuss the importance of well‐curated reference databases that remain to be developed in the future.